ABSTINENSI DAN PENDIDIKAN SEKS REMAJA SURVEI CEPAT DI JAKARTA DAN SEKITARNYA - NURFADHILAH NURFADHILAH; RR Arum Ariasih (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2019)
Indonesian teenagers are getting smarter and having higher achievements, yet experiencing disadvantage situation. Surveys revealed that their health knowledge/literacy and behavior are not getting better even though information access raising. Education (intra and extra curricula) is one of strongest strategy to intervene the fundamental problems. A rapid survey was conducted to assess abstinence and the need of sex education for adolescents in Jakarta and surrounding areas. Data were collected from 163 respondents interviewed at their schools or community. As much as 65% said they never had any kind of sexual activity (primary abstainers) and 81.6% said they need sex education with an offline (face to face) methode 47.8%. Adolescent’s sexual education in Indonesia is indeed an urgent need. An integrative and comprehensive sex education along with adolescent (and pre-adolescent) developmental stages, cultural, and religious values regarding the affect on future health should be undertake.